De receptie van de tentoonstelling ‘Met de dood in de ogen’ in de Grote Kerk te Leeuwarden - Steensma, Regnerus (Jaarboek voor liturgieonderzoek, 1992)
In 1991 an exhibition was held in the "Grote Kerk" (a Reformed church) in Leeuwarden under the title of: "Being close to death". This was an exhibition of modern art relating to the theme dying, death and mortality. By request of the "Committee Church and Art of the Reformed Parish in Leeuwarden" the exhibition was made up by the Institute for Liturgy Research of the state university of Groningen. By means of an inquiry an investigation was made into the reception of the works of art by the visitors...